The association of self-perceived changes due to COVID-19 with mental and physical health among adult primary care patients with multiple chronic conditions: A US-based longitudinal study - Levi N Bonnell; Jessica Clifton; Lisa W Natkin; Juvena R Hitt; Benjamin Littenberg (Journal of Multimorbidity and Comorbidity)
Introduction This study explores the association between self-perceived personal and community changes due to COVID-19 and health among vulnerable primary care patients experiencing multiple chronic conditions. Methods Between September 2017 and February 2021, we obtained data from 2,426 primary care patients managing multiple chronic conditions from across the United States. We assessed the relationship between self-perceived personal and community changes due to COVID-19 and change in health measured by the PROMIS-29 mental and physical health summary scores, GAD-7 (anxiety), andPHQ-9 (depression), and DASI (functional capacity) adjusting for relevant demographic, neighborhood characteristics, and county covariates. Results After adjustment, self-perceived personal and community changes due to COVID-19 were associated with significantly worse mental health summary scores (ß = -0.55; 95% Confidence Interval (CI) = -0.72, -0.37), anxiety (ß = 0.28; 95% CI = 0.16, 0.39), depression (ß = 0.35; 95% CI = 0.22, 0.47), and physical health summary scores (ß = -0.44; 95% CI = 0.88, 0.00). There was no association with functional capacity (ß = - 0.05; 95% CI = -0.16, 0.05). Discussion Among adults managing multiple chronic conditions, self-perceived personal and community changes due to COVID-19 were associated with health. This vulnerable population may be particularly susceptible to the negative effects of COVID-19. As we do not know the long-term health effects of COVID, this paper establishes a baseline of epidemiological data on COVID-19 burden and health among primary care patients with multiple chronic conditions.